2013
DOI: 10.1021/ef4012615
|View full text |Cite
|
Sign up to set email alerts
|

Biogasoline Production from the Co-cracking of the Distilled Fraction of Bio-oil and Ethanol

Abstract: In view of the severe coke formation and catalyst deactivation during crude bio-oil cracking, an innovative cracking technology based on bio-oil molecular distillation is proposed. The distilled fraction (DF) from bio-oil molecular distillation is enriched with small molecular acids and ketones and has enhanced cracking behavior compared to crude bio-oil. The influence of the reaction temperature, pressure, and the DF/ethanol ratio in the feed was studied. It was found that co-cracking of the DF and ethanol pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 27 publications
0
49
0
1
Order By: Relevance
“…Furthermore, the upgraded oils showed a higher degree of deoxygenation with a quite high heating value and a good combustibility. The upgrading of pyrolysis oil derived from rice husk was investigated by Wang et al (2013). They outlined a unique technique to produce highquality gasoline rich with aromatic hydrocarbons by using a distilled fraction of the pyrolysis oil with ethanol and investigated their co-cracking behaviour using the HZSM-5 catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the upgraded oils showed a higher degree of deoxygenation with a quite high heating value and a good combustibility. The upgrading of pyrolysis oil derived from rice husk was investigated by Wang et al (2013). They outlined a unique technique to produce highquality gasoline rich with aromatic hydrocarbons by using a distilled fraction of the pyrolysis oil with ethanol and investigated their co-cracking behaviour using the HZSM-5 catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The authors' previous study showed that the major components in the bio-oil distilled fraction were acids and ketones, with the total contents approximately 48.6% and 27.5%, respectively (Wang et al 2013b). In particular, HAc, HPO, and CPO derivatives were the typical compounds, with relative contents of 23.9%, 27.9%, and 5.1%, respectively.…”
Section: Methodsmentioning
confidence: 97%
“…The studied hydrogenation temperatures were 200 °C, 250 °C, and 300 °C, which were typically used in the hydrogenation study of bio-oil chemicals (Elliott and Hart 2009). The cracking temperature was set at 400 °C, which was a suitable cracking temperature for the generation of aromatic hydrocarbons as concluded by a previous study (Wang et al 2013b).…”
Section: Catalytic Reactionmentioning
confidence: 99%
See 2 more Smart Citations